THE EFFECT OF PROMOTION, PRICE, AND FACILITIES ON CUSTOMER SATISFACTION (A CASE STUDY AT RESTO THE LOBBY) - Rohani; Husnawati Rahman; Sultan Iskandar; Ikhsan Amar Jusman (Bajang Institute, 2021)
The purpose of this study was to determine the effect of promotion, price, and facilities on customer satisfaction at Resto the Lobby. In this study, the researcher applied the qualitative method with a quantitative approach. In addition, the employed sampling technique was purposive sampling, resulting in 75 people as respondents. The collected data were analyzed using the reliability test, multicollinearity test, linear regression analysis, T-test, and F-test with SPSS v. 22. Results showed that promotion, price, and facilities simultaneously have a positive and significant effect on customer satisfaction. Partially, prices and facilities have a positive and significant effect on customer satisfaction. However, promotion partially has no effect on customer satisfaction